Soviet Historiography and the Concept of Man - Barbu, Zvedei (Estudos Universitários)
Few ideas had a more agitated and dramatic history in Soviet Russia than the idea of history itself. This may come as a surprise and disappointment to those who believe that K. Marx laid the concept of history on sound materialistic foundations, and that as a result of this lie offered an unambiguous solution to the entangled problem concerning the relation between man and history.